Internet Health Resources on Nocturnal Enuresis: A Readability, Quality, and Accuracy Analysis - Fung, Adrian C.H.; Lee, Matthew H.L.; Leung, Jessie L.; Chan, Ivy H.Y.; Wong, Kenneth K.Y. (European Journal of Pediatric Surgery, 2023)
Introduction Nocturnal enuresis is a common yet quality-of-life-limiting pediatric condition. There is an increasing trend for parents to obtain information on the disease's nature and treatment options via the internet. However, the quality of health-related information on the internet varies greatly and is largely uncontrolled and unregulated. With this study, a readability, quality, and accuracy evaluation of the health information regarding nocturnal enuresis is carried out.Materials and Methods A questionnaire was administered to parents and patients with nocturnal enuresis to determine their use of the internet to research their condition. The most common search terms were determined, and the first 30 websites returned by the most popular search engines were used to assess the quality of information about nocturnal enuresis. Each site was categorized by type and assessed for readability using the Gunning fog score, Simple Measure of Gobbledygook (SMOG) index, and Dale–Chall score; for quality using the DISCERN score; and for accuracy by comparison to the International Children's Continence Society guidelines by three experienced pediatric urologists and nephrologists.Results A total of 30 websites were assessed and classified into five categories: professional (n = 13), nonprofit (n = 8), commercial (n = 4), government (n = 3), and other (n = 2). The information was considered difficult for the public to comprehend, with mean Gunning fog, SMOG index, and Dale–Chall scores of 12.1 ± 4.3, 14.1 ± 4.3, and 8.1 ± 1.3, respectively. The mean summed DISCERN score was 41 ± 11.6 out of 75. Only seven (23%) websites were considered of good quality (DISCERN score > 50). The mean accuracy score of the websites was 3.2 ± 0.6 out of 5. Commercial websites were of the poorest quality and accuracy. Websites generally scored well in providing their aims and identifying treatment benefits and options, while they lacked references and information regarding treatment risks and mechanisms.Conclusion Online information about nocturnal enuresis exists for parents; however, most websites are of suboptimal quality, readability, and accuracy. Pediatric surgeons should be aware of parents' health-information-seeking behavior and be proactive in guiding parents to identify high-quality resources.
Keywords: internet information; enuresis; pediatric; readability; quality